Salvia semiscaposa (Lamiaceae) a new species from Nanchititla, Mexico - Fragoso-Martínez, Itzi; Martínez-Gordillo, Martha; de Luna, Efraín (Phytotaxa, 2015)
A new species of Salvia section Lavanduloideae from the Estado de México is described and illustrated. Salvia semiscaposa is a procumbent plant morphologically similar to S. scaposa and S. helianthemifolia. It differs from the former by having mostly obovate leaf blades, more than six flowers per verticillaster and posterior calyx lobes narrower and apiculate. On the other hand, S. helianthemifolia differs from the new species by the presence of an erect stem, ovate leaves and trichomes on the calyx surface distributed only on the veins.